Comparison of Lifetime Suicide Attempts and Recent Suicidal/Self-Harming Thoughts Among Sexual Minority and Heterosexual Utahns: Results from a Population-Based Survey. Issue 2 (3rd April 2022) - McGraw, James S.; Peer, Samuel O.; McManimen, Stephanie; Chinn, Jessica; Mahoney, Annette
Abstract: Objective: We sought to be the first published article to report differences in population-representative prevalence of suicidal thoughts and attempts by sexual orientation. Method: Data from Utah's Behavioral Risk Factor Surveillance System (BRFSS) collected for 2016 ( N  = 10, 988) and 2017 ( N  = 10, 251) were examined to determine differences in the prevalence of suicidal thoughts in the past 2 weeks and the lifetime prevalence of suicide attempts (i.e., any, single, and multiple) by sexual orientation. Results: 3.5% of heterosexuals Utahns reported recent suicidal/self-harming thoughts in the last 2 weeks compared to 14.7% of LGB Utahns (OR = 4.73 95% CI [2.67, 8.36]). 5.8% of heterosexuals reported a lifetime prevalence of any suicidal attempts compared to 37.2% of LGB folx (OR = 9.58 95% CI [7.16, 12.81]) with similar differences occurring for single and multiple attempts. Comparing LG versus B, there was no difference in ideation or prevalence of any attempt, but bisexuals reported higher rates of multiple suicide attempts. Conclusion: LGB folx in Utah are drastically more likely to have thought about suicide/self-harming in the last 2 weeks and to have attempted suicide in their lifetime when compared to heterosexuals in Utah.